A study on asymptomatic bacteriuria in pregnancy: prevalence, etiology and comparison of screening methods - Mukherjee, Kheya; Golia, Saroj; CL, Vasudha; ., Babita; Bhattacharjee, Debojyoti; Chakroborti, Goutam (International Journal of Research in Medical Sciences, 2017)
Background:Asymptomatic bacteriuria is common in women with prevalence of 4-7% in pregnancy. The traditional reference test for bacteriuria is quantitative culture of urine which is relatively expensive time consuming and laborious. The aim of this study was to know the prevalence of asymptomatic bacteriuria in pregnancy, to identify pathogens and their antibiotic susceptibility patterns and to device a single or combined rapid screening method as an acceptable alternative to urine culture. Methods:Clean catch mid-stream urine were collected from 250 pregnant women aged between 18-45 years attending antenatal clinic, for a period of one year (November 2008-2009). Screening tests such as gram staining of uncentrifuged urine, pus cell count, nitrite test and leukocyte esterase test were done. Identification of organisms and antibiotic sensitivity tests were performed as per standard methods. Results:Out of the 250 pregnant women, 21 (8.4%) had significant bacteriuria. High percentage of asymptomatic bacteriuria was seen in 2nd trimester (42.86%) and in primigravidas (52.38%). E. coli (57.14%) was the most common organism. Among screening tests gram staining of uncentrifuged urine had a sensitivity of 85.71%. Nitrite and leukocyte esterase tests alone showed sensitivity of 71.42%. However, the combination of these two tests, either tests positive, showed sensitivity and negative predictive value of 90.47% and 99.09% respectively. Conclusion:Asymptomatic bacteriuria in pregnancy can be identified by simple and combined rapid screening methods and urine culture along with antibiogram so that early treatment can be started thereby preventing complications.